Phytochemical profiling and in silico evaluation of Artemisia absinthium compounds targeting Leishmania N-myristoyltransferase: molecular docking, drug-likeness, and toxicity analyses - Boudou, Farouk; Belakredar, Amal; Berkane, Alaeddine; Keziz, Ahcen; Alsaeedi, Huda; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2024)
Background Artemisia absinthium has long been recognized for its therapeutic properties against various diseases. Among these is leishmaniasis, a parasitic infection that remains a global health challenge. Targeting Leishmania N-myristoyltransferase (NMT), a crucial enzyme for parasite survival, represents a promising therapeutic approach. The bioactive compounds in A. absinthium could potentially inhibit NMT and serve as new treatment options for leishmaniasis. Aim This study aims to investigate the phytochemical composition, drug-likeness, and molecular dynamics of A. absinthium bioactive compounds targeting Leishmania NMT, identifying potent inhibitors that could serve as new drug candidates. Method The extract of A. absinthium was analyzed using High-Performance Liquid Chromatography (HPLC), identifying nine phenolic compounds, with kaempferol (10.72%) and chlorogenic acid (4.43%) being the most abundant. Drug-likeness and toxicity were evaluated using SwissADME and OSIRIS Property Explorer, focusing on adherence to Lipinski’s rule of five and Ghose’s filter. Molecular docking studies were conducted to evaluate the binding affinity of these compounds to NMT. Molecular dynamics (MD) simulations were performed to assess the stability and flexibility of the NMT-apigenin complex. Results Molecular docking identified apigenin as the most potent NMT inhibitor, with a binding energy of −9.6 kcal/mol, forming significant hydrogen bonds with threonine residues 203 and 189. Drug-likeness analysis revealed that most compounds adhered to Lipinski’s rule of five, indicating favorable pharmacokinetic properties. MD simulations confirmed the stability of the NMT-apigenin complex, with root mean square deviation (RMSD) values of 0.04 nm, root mean square fluctuation (RMSF) values between 0.05 and 0.35 nm, and radius of gyration (Rg) values ranging from 2.24 to 2.30 nm. Normal mode analysis further supported the complex’s stability and flexibility. Conclusion The findings of this study underscore the potential of Artemisia absinthium compounds, particularly apigenin, as promising candidates for the development of new anti-leishmaniasis drugs. The potent inhibition of Leishmania NMT by apigenin, along with its favorable pharmacokinetic and stability profiles, supports its further exploration in antileishmanial drug development.